10.1016/S0271-7964(08)70724-9 (CrossRef Listing of Deleted DOIs, 2000)
AIM: To identify latent profiles of perceived workplace violence climate (PWVC) among nurses in tertiary hospitals and explore central network characteristics across profile groups. DESIGN: A cross-sectional study. METHODS: A multicentre cross-sectional study was conducted from July to September 2023 among 2064 nurses from eight tertiary hospitals across eight provinces in China. Data were collected using the Nurses' PWVC Scale, Clinical Communication Ability Scale, and Emotional Intelligence Scale. Latent Profile Analysis (LPA) identified heterogeneous subgroups, multinomial logistic regression examined factors associated with profile membership, and network analysis explored central and bridge nodes. RESULTS: The prevalence of workplace violence (WPV) exposure was 82.4%. Three distinct PWVC profiles were identified: Vulnerable-Sensitive (17.0%), Stable-Perceptive (48.3%), and Resource-Empowered (34.7%). Nurses classified within the Resource-Empowered profile generally demonstrated higher emotional intelligence, stronger communication ability, better health status, and more frequent participation in violence-prevention training. Network analysis identified profile-specific central nodes, including violence-prevention visibility, management responsiveness, and post-incident managerial support, while individualised risk assessment emerged as a key bridge node across networks. CONCLUSION: PWVC among nurses demonstrates substantial heterogeneity across profile groups. Findings suggest that organisational strategies addressing management responsiveness, violence-prevention visibility, and individualised risk assessment may help strengthen perceived workplace safety, particularly among nurses with less favourable perception profiles. IMPACT: This study identifies distinct violence climate profiles among nurses and highlights several central network components that may represent potential organisational intervention targets. These findings may support the development of more tailored workplace violence prevention strategies within nursing management contexts. PATIENT OR PUBLIC CONTRIBUTION: No patient or public contribution.